Effects Boswellia carterii Gum Resin Fractions on Intact Memory and Hyoscine-induced Learning Impairments in Rats Performing the Morris Water Maze Task - H Hosseinzadeh; M Ramezani; Y Akhtar; T Ziaei (Institue of Medicinal Plants, ACECR, 2010)
Background: In traditional medicine, a gum resin obtained from Boswellia carterii, has been used as an agent for enhancing memory and learning abilities. Objective: In the present research, the effect of fractions obtained from gum resin of Boswellia carterii was assessed on enhancement of memory in intact and on memory impairments induced in rats by hyoscine using the Morris water maze task. Methods: The ethyl acetate (0.1 mg/kg) and N-butanol (0.1 mg/kg) fractions were injected intraperitoneally to rats 1 h before training for 5 consecutive days. During the training period, four trials were carried out each day. On the 5th day of the experiment, the locomotor activity was assessed using open field test. The effect of ethyl acetate fractions was evaluated on memory impairment induced by hyoscine (0.5 mg/kg). Results: The ethyl acetate (0.1 mg/kg) and N-butanol (0.1 mg/kg) fractions showed significant effects in enhancing the memory ability in intact rats. This effect was much significant with ethyl acetate fraction (p<0.001). The ethyl acetate (0.1 mg/kg) fraction reduced the deficit effect of hyoscine on memory (p<0.001). The N-butanol and ethyl acetate fractions (0.1 g/kg) have no effect on locomotor activity. Conclusion: On the basis of these results, B. carterii gum resin improved intact memory and the hyoscine impaired acquisition/performance activity. This effect may be mediated via cholinergic system.